2011
DOI: 10.3184/096034011x13182685579795
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Young’s modulus of oxides at high temperature related to the oxidation study

Abstract: a-Al 2 O 3 , Cr 2 O 3 , and a-Fe 2 O 3 specimens were prepared by a sintering process. A 400 -1000-Hz sine wave was applied to the specimen at 290 -1273 K. The applied and respond waves were monitored by using force and acceleration sensors. The intensity ratio and phase shift between the applied and respond waves were analysed, and the anti-resonance frequency was obtained. Young's moduli of a-Al 2 O 3 , Cr 2 O 3 , and a-Fe 2 O 3 are estimated to be 386, 286, and 220 GPa at 298 K, respectively. The temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…When the deposition pressure was in the range of 1-0.29 Pa, the chromium oxide coatings had an average hardness and Young's modulus value of about 5 and 80 GPa, respectively. This result is consistent with Figure 6 in Kao's [4] research, in which chromium oxide coatings showed a low hardness value of 8 GPa when deposited at a process pressure between 0.5-2.5 Pa. Decreasing the operation pressure to 0.16 Pa, the hardness and Young's modulus of the coatings increased significantly and reached an average hardness and Young's modulus value of about 25 and 289 GPa, respectively, which is near the bulk Cr2O3 values reported in previous literature [1][2][3][4]34]. According to structural analysis results, it can be inferred that the low hardness of the chromium oxide coatings deposited at higher pressures was due to the formation of mixed chromium oxide phases.…”
Section: Mechanical Properties Of Coatingssupporting
confidence: 70%
“…When the deposition pressure was in the range of 1-0.29 Pa, the chromium oxide coatings had an average hardness and Young's modulus value of about 5 and 80 GPa, respectively. This result is consistent with Figure 6 in Kao's [4] research, in which chromium oxide coatings showed a low hardness value of 8 GPa when deposited at a process pressure between 0.5-2.5 Pa. Decreasing the operation pressure to 0.16 Pa, the hardness and Young's modulus of the coatings increased significantly and reached an average hardness and Young's modulus value of about 25 and 289 GPa, respectively, which is near the bulk Cr2O3 values reported in previous literature [1][2][3][4]34]. According to structural analysis results, it can be inferred that the low hardness of the chromium oxide coatings deposited at higher pressures was due to the formation of mixed chromium oxide phases.…”
Section: Mechanical Properties Of Coatingssupporting
confidence: 70%
“…The previous reports have indicated the Cr 2 O 3 thin films possess a high hardness of over 20 GPa [ 10 , 14 , 15 , 30 , 31 , 32 ]. In some conditions the processes produced chromia with lower hardness, even down to an 8–10 GPa level [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of a built‐in α‐Al 2 O 3 protection network is inevitable to raise the elastic modulus of TBCs structure (Figure 6 ) attributed to coating porosity reduction and introduction of stiffer Al 2 O 3 ( E Al2O3 ≈386 GPa; [ 48 ] E YSZ ≈205 GPa). This work investigated the effect of injected Al 2 O 3 on the Young's modulus of TBCs, and the effect of drip coating times on the Young's modulus of TBCs.…”
Section: Discussionmentioning
confidence: 99%